Exploring Energy Modelling in Architecture Logics of Investment and Risk. (March 2017) - Oliveira, Sonja; Marco, Elena; Gething, Bill; Robertson, Craig
Abstract: This paper examines the ways architects negotiate new early stage design energy modelling tools in their design practice. Energy modelling tools have traditionally mostly been usedby building services engineers with their engagement often occurring at late stages in design to largely verify and validate already established ideas. Recently, however, with a growing international energy agenda and development of new modelling technologies there has been a greater need for broadening use particularly with architects early in design. Yet despite the broadening of use, and increased importance placed on building performance, few studies account for the ways new groups of users such as architects negotiate use of new energy modelling tools in their design practice. Research on the topic of energy modelling has tended to focus on addressing improvements within a particular professional domain or in enhancing features within tools and providing better analysis parameters. The data draws on semi structured interviews and focus group sessions with 26 participants across 4 large international architecture firms in the UK. Preliminary findings indicate differing organizational principles as well as team identities and project assumptions on the ways energy modelling contributes or detracts from fulfilling overall project needs. The implications of the findings are twofold. First, the analysis provides an initial overview of how early stage design energy modelling is considered in design in architecture practice in the UK. Second, the paper provides an understanding of how architects negotiate meaning on energy in design. There are also implications for energy policy development in the context of the built environment particularly concerning building performance.